2007
DOI: 10.1100/tsw.2007.48
|View full text |Cite
|
Sign up to set email alerts
|

From the Behavioral Pharmacology of Beta-Carbolines to Seizures, Anxiety, and Memory

Abstract: A number of beta-carbolines are inverse agonists of the GABA-A receptor complex, acting on the benzodiazepine site. They show convulsive properties when administered at high doses, anxiogenic properties at moderate doses, and learning-enhancing effects at low doses. These data suggest a possible physiological relationship, through the GABA-A receptor channel, between memory processes, anxiety, and ultimately, in pathological states, epileptic seizures. This relationship seems to be confirmed partially by exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 119 publications
(155 reference statements)
2
21
0
Order By: Relevance
“…In conclusion, the effect of NO on learning and memory is dose dependent. Confirming our results, Venaultet al has shown that low doses of β-carboline alkaloids improve learning and memory retention [26].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In conclusion, the effect of NO on learning and memory is dose dependent. Confirming our results, Venaultet al has shown that low doses of β-carboline alkaloids improve learning and memory retention [26].…”
Section: Discussionsupporting
confidence: 92%
“…The dose of β-carboline required for enhancing memory is usually lower than the dose required for eliciting anxiogenic actions [5,26] and this rule was replicated in our study. Confirming our results, Samardˇzi´c et al have shown that DMCM, a benzodiazepine site inverse agonist, at the dose of 0.1 mg/kg improves active avoidance in the rats [1].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In the human body, the b-carbolines may be formed from the biogenic amines tryptamine and 5-HT through condensation with aldehydes or a-keto acids (Talhout et al, 2007;Rook et al, 2010). Several investigations indicate a wide spectrum of therapeutic activities for the b-carbolines such as antinociceptive effect (Nenaah, 2010), neuroregulatory effect (Munoz et al, 2000;Splettstoesser et al, 2005;Moura et al, 2006), antibiotic properties (Martin et al, 1997;Hamsa and Kuttan, 2010;Yang et al, 2011), antidepressant-like effect (Herraiz and Chaparro, 2005), learning processes (Venault and Chapouthier, 2007), and excitation (Rommelspacher et al, 1980). The b-carboline alkaloids may act in biological tissues, such as the heart, kidney, liver and brain tissue (Ruiz-Durantez et al, 2001;Splettstoesser et al, 2005;Moura et al, 2006;Rook et al, 2010;Nasehi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…They can translate into an immobilisation, a "falling back" of the animal on itself ("freezing") or, at the contrary, into an active motor response like flight or fight. In many cases, in the mouse for example, the aggressive tendency is correlated to anxiety (Guillot & Chapouthier, 1996), but there are exceptions (Venault & Chapouthier, 2007). These fear, anxiety, and stress mechanisms can be found in most animals, in all vertebrates in particular.…”
Section: Introductionmentioning
confidence: 99%